A REVIEW ON ENVIRONMENTAL EDUCATION FOR THE AMELIORATION OF ENVIRONMENTAL CHALLENGES AND ATTAINMENT OF SUSTAINABILITY OF THE NIGERIAN ENVIRONMENT - UMAR AHMAD, YUSUF; ADAMU, USMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This study attempts to review the importance and application of Environmental Education as well its types and sources in Nigeria with the view to making people more conscious towards proper utilization of environmental resources. Similarly, the study reviews the efforts made by Nigerian government towards safeguarding the environment in order to attain sustainability. However, the review revealed that most of the environmental laws and regulations were not enforced at various stages, as such degrades the quality of the environment. While the study recommended the enforcement of the environmental laws and regulations, it further recommended that environmental education (EE) should be incorporated into the National Curriculum or captured in some subject areas such as Social Studies, Hygiene, Basic Science, etc. of the National Curriculum. Lastly, the paper recommended the use of seminars, conferences, workshops, and media, among others can go a long way in educating and re-educating people about their environment. Keywords: